Efek Level Sari Serabut Buah Lontar (Borassus Flabellifer Linn) dalam Pengencer Sitrat Kuning Telur terhadap Kualitas Semen Beku Babi Peranakan Landrace - Maria Indriyati Juita Adal; Wilmintje M. Nalley; Ni Made Paramita Setyani; Kirenius Uly (Pusat riset dan Inovasi Nasional, 2026)
This study aims to determine the effect of palm oil fiber (PFFE) (Borassus flabellifer Linn.) levels in egg yolk citrate diluent (C-EY) on the quality of frozen semen from landrace crossbred boar. The material used was fresh semen from 3 landrace crossbred pigs aged 2-3 years. The experimental method was a Completely Randomized Design consisting of five treatments and five replications. T0 = S-KT, T1= C-EY + PFFE 0.75%, T2 = C-EY + PFFE 1.5%, T3 = C-EY + 2.25% PFFE, and T4 = C-EY + PFFE 3%, and the addition of 6% glycerol in each treatment. The parameters observed included motility, viability, abnormalities, and recovery rate of spermatozoa. The data obtained were analyzed using analysis of variance (ANOVA) and analysis using SPSS version 27. The results revealed that the addition of PFFE had a significant effect (P <0.05) on post-thawing semen motility. With a value of T2: 24.00±2.23%, followed by T3: 15.00±5.00%, T1: 14.00±6.51%, T4: 13.00±4.47% and T0: 12.00±7.58%. Post-thawing viability also revealed that the addition of palmyra fruit fiber extract had a significant effect (P<0.05) with a T2 value of 46.65±3.65% followed by treatment T3: 25.70±6.75, T1: 24.69±8.70, T4:24.24±7.81 and T0: 22.36±8.67. While semen abnormalities did not have a significant difference between treatments. It can be concluded that the use of 1.5% SSBL and S-KT resulted in the highest post-thaw semen motility in treatment P2, with a value of 24.00 ± 2.23% in crossbred Landrace boar semen.